THE IMPLEMENTATION OF LITERACY ACTIVITY ON STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT OF THE NINTH GRADE STUDENTS AT SMP NEGERI 3 PALANGKA RAYA IN SCHOOL YEAR 2019/2020 - Hamzah, Zulfikar; Karani, Elanneri; Usadiati, Wahjuningsih (Journal Compound: Improving the Quality of English Education, 2020)
This research was conducted through a descriptive qualitative method to find out the implementation of literacy activities on students' reading of descriptive text of the ninth grade students at SMP Negeri 3 Palangka Raya. The research wanted to know the process of literacy activities in two classes, i.e. the ninth grade room seven and the ninth grade room eight by using observation sheets, questionnaire, field notes obtained from the students’ journals, and tasks of reading comprehension. The results show that: 1) the literacy activities of the ninth (IX) grade room seven and ninth (IX) grade room eight of SMP Negeri 3 Palangka Raya were done at the time of implementation, place of implementation, types of activities, types of the title of description text and follow-up activities as follows: the timing for the implementation of literacy activity was on time according to the schedule. All students carried out the literacy activities and they started recording literacy activities in their journals. The sources of the texts that read by the students were English Textbooks containing the English Descriptive Texts to be read until finish. The process of reading for literacy activities was centralized, i.e. at the ninth (IX) grade room seven and ninth (IX) grade room eight of SMP Negeri 3 Palangka Raya; 2) The description of the students in their reading habits of the ninth (IX) grade students room seven and the ninth (IX) grade students room eight room were written in the field – notes (Students’ Journal). The description included date or day of the literacy activity, title or writer of the text, page of the text, date, and comments written by the students in Indonesian language in based on the Minister of Education of Republic Indonesia’s version and completed with the summary; 3) the problems faced by the students of the Ninth (IX-7) Grade Room Seven and the Ninth (IX-8) Grade Room Eight in SMP Negeri 3 Palangka Raya were stated in medium, hard, and very hard columns about the reading comprehension texts used in literacy activities, and these problems were used as references for the English teachers to evaluate again the students’ reading comprehension of English descriptive text; and 4) from the 26 students’ scores of the ninth (IX) grade room seven and 24 students in the ninth (IX) grade room eight who followed the post-literacy reading comprehension task, there was 4% or only 1 student in each room who has completed and fulfilled the criteria of minimum of mastery or KKM.